A Study of Marketing Mix on McDonald’s: Evidence from Malaysia - Tan, Xin Yan; Qi Tan, Jia; Tan, Jing Wen; Tan, Xuan Wei; Kee, Daisy Mui Hung (The Global Academia Publisher, 2024)
McDonald's is a leading fast-food company popular among Malaysians. Due to the increasing work pace and the desire for idleness, the consumer demand for a quick yet convenient meal grows steadily. This study focuses on the marketing mix of 4Ps implied by McDonald's, including product, price, promotion, and place in order to position itself in the competitive market of the fast-food industry. The objective of this study is to analyse the marketing performance of McDonald's while suggesting further improvements based on the significant factors. A total of 200 McDonald's customers completed the online survey through Google Forms. The results indicate that McDonald's is a highly reputed fast-food restaurant in Malaysia while showing that the customer satisfaction with the innovations and localization of the products and services it offers are the key factors of marketing performance. This study suggests certain implications based on the significant element to improve the marketing performance.